2020
DOI: 10.1093/aob/mcaa022
|View full text |Cite
|
Sign up to set email alerts
|

Mutational analysis indicates that abnormalities in rhizobial infection and subsequent plant cell and bacteroid differentiation in pea (Pisum sativum) nodules coincide with abnormal cytokinin responses and localization

Abstract: Background and Aims Recent findings indicate that Nod factor signalling is tightly interconnected with phytohormonal regulation that affects the development of nodules. Since the mechanisms of this interaction are still far from understood, here the distribution of cytokinin and auxin in pea (Pisum sativum) nodules was investigated. In addition, the effect of certain mutations blocking rhizobial infection and subsequent plant cell and bacteroid differentiation on cytokinin distribution in nod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
21
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 81 publications
2
21
0
1
Order By: Relevance
“…Recently, it was demonstrated that cytokinins control the rearrangement of cortical microtubules from transverse orientation in the transition and elongation zones to oblique orientation in the differentiation zone in the epidermal cells of A. thaliana root [ 47 ]. Intriguingly, the localization of auxin in the symbiotic nodules of L. japonicus [ 48 ] and P. sativum [ 49 ] is limited to the meristem and vascular tissues. Active accumulation of cytokinins was observed in P. sativum nodules not only in the meristem, but also in the infection zone and the distal part of the nitrogen fixation zone [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it was demonstrated that cytokinins control the rearrangement of cortical microtubules from transverse orientation in the transition and elongation zones to oblique orientation in the differentiation zone in the epidermal cells of A. thaliana root [ 47 ]. Intriguingly, the localization of auxin in the symbiotic nodules of L. japonicus [ 48 ] and P. sativum [ 49 ] is limited to the meristem and vascular tissues. Active accumulation of cytokinins was observed in P. sativum nodules not only in the meristem, but also in the infection zone and the distal part of the nitrogen fixation zone [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…Approximately 50–100 mg of ground plant tissue was used for RNA extraction, as previously described [ 39 ]. Around 1–2.5 μg of total RNA was used to synthesize cDNA using 20 μL RevertAid Reverse Transcriptase (Thermo Fisher Scientific, USA), and then the cDNA samples were diluted to 1:10.…”
Section: Methodsmentioning
confidence: 99%
“…These include enzymes such as the E3 ubiquitin ligase in L. japonicus [ 87 ], the putative E3 ubiquitin ligase with the Nodule specific RING finger domain (LjnsRING) in L. japonicus [ 163 ], the E3 ubiquitin ligase with ‘zinc finger’ type domain, Seven in absentia (MtSINA) in M. truncatula [ 164 ] and Cystathionine-β-synthase-like1 (MtCBS1) in M. truncatula [ 165 ]. Recently, using pea gibberellin-deficient and della -deficient mutants, it was shown that the phytohormone gibberellin suppresses the formation of infection threads [ 166 ], and its amount in infection threads is much lower than in bacteroids [ 167 ], on the contrary, phytohormones cytokinins and auxins play an important role in the development and propagation of infection threads, as well as in the release of bacteria from infection droplets [ 132 , 168 , 169 , 170 ]. A putative role of ethylene in infection thread maturation was also suggested [ 171 ].…”
Section: Propagation Of the Infection Threadmentioning
confidence: 99%